Recurrence rate of sphenoid wing meningiomas and role of peritumoural brain edema: a single center retrospective study - Nassar, Abdalrahman M.; Smolanka, Volodymyr I.; Smolanka, Andriy V.; Murzho, Evelina Z.; Chaulagain, Dipak (Ukrainian Neurosurgical Journal, 2021)
Objective: To evaluate the recurrence rate of the operatively treated sphenoid wing meningiomas (SWMs) in relation to other factors and role of PTBE in recurrence as a prognostic factors in a series of 67 patients. Materials and methods: The magnetic resonance imaging (MRI), and pathology data for 67 patients with SWM, who underwent surgery at Uzhhorod Regional Neurosurgical Center between 2007 and 2021 were examined. The recurrence rate and role of PTBE in recurrence in relation to: gender, age, extend of resection, histopathology, tumor volume, location and time of recurrence were evaluated. Follow-up period ranged from 6 to 168 months (median, 87 months) after surgical resection. Results: In our study, the mean age of patients is 47 years, ranged (20-74), at the average (53.5). Male 16 (23.9%), female 51 (76.1%). Mean tumor volume was (32.8cm3), ranged 4.2cm3-143.7cm3. Edema Index (EI) 1; 27 (40.3%) absent edema, and (EI) >1; in 40 (59.7%) present edema. Recurrence rate was 11 (16.4%) patients, 8 (20.0%) patients with PTBE, as compared to 3 (11.1%) patients without PTBE, (p=0,50). Female (8 patients, 15.7%), male (3 patients, 18.7%). The mean age of recurrence was 50.9 years, ranged (21-75), at the average 52.0 years. The mean age in female was 50.8 years, in male 51.0. Bivariate analysis of simultaneous effect of gender and age on SWM recurrence with logistic regression yield both main effect and interaction effect (β gender=M=7.56±6.44, P=0.24; β age=-0.034±0.031, p=0.28; β interaction term=-0.13±0.12, p=0.26). Out of 11 recurrence cases, (2 cases, 9.5%) with small tumour volume, (5 cases, 15.6%) with medium, (3 cases, 33.3%) with large, and (one case, 20.0%) with giant tumour volume. The effect of tumour volume on recurrence rate is insignificant, χ2=2.42, p=0.49.Location of SWM; the recurrence was in (6 cases, 25.0%) of CM location, (2 cases, 25.0%) of SOM and (3 cases, 11.5%) in lateral SWM, (p=0.19). Pathological grade, in the low grade (Gr.I) 7 recurrence cases (13.0%), as compared to 4cases (44.4%) in atypical Gr II, (p=0.01). Simpson grade, the recurrence rate was; 0% in Gr. I; 13.9% in Gr. II; 20.0% in Gr.III; and 33.3% in Gr. IV and 3 cases had died in the early post op (p<0.05). Conclusion: The factors which had a strong impact on the recurrence rate in our study,; i) pathological grade (Gr. II, atypical type) p=0.01 and ii) Simpson grade (extend of tumor resection, p<0.05), while, PTBE (P=0.50), tumor volume (χ2=2.42, p=0.49) and location (χ2=3.37, p=0.19), are weak and non strong factors for recurrence. However, time of recurrence is shorter in patients with PTBE (W=20.5, p=0.092). WHO Gr. II (Spearman’s p=-0.86, p=0.00063) and negligible for Simpson grade (Spearman’s=-0.15, p=0.66).